Phytochemical and Biological Investigation of Curcuma amada Leaves: Phytochemical and biological Investigation of Curcuma amada - Hossain, Md Sakhawat; Rahaman, Md Mostafizur; Rahman, Md Atikur; Uddin, Jalal; Ahmed, Firoj (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Methanolic extract of Curcuma amada leaves was investigated for isolation of secondary metabolites by successive chromatographic separation (VLC, column chromatography and TLC) which yielded several purified compounds. Among them the structures of β-sitosterol and stigmasterol were determined by analysis of high resolution 1H NMR spectroscopic data and co-TLC with authentic samples. The crude methanolic extract of C. amada leaves and its different fractionates i.e. petroleum ether (PESF), chloroform (CSF) and aqueous (AQSF) soluble fractions were evaluated for antibacterial, antioxidant, cytotoxic and thrombolytic activities. In antibacterial screening, the CSF exhibited the highest inhibition against bacterial growth having zone of inhibition 12 mm compared to the standard kanamycin where the zone of inhibition was observed at 18 mm against gram negative Vibrio mimicus. Significant free radical scavenging activity was also exhibited by CSF with the IC50 value of 103.09 μg/ml as compared to tert-butyl-1-hydroxytoluene (BHT) having IC50 31.88 μg/ml. In cytotoxicity study, the crude extract showed significant lethality towards brine shrimp having with the LC50 value of 6.540 μg/ml as compared to the standard vincristine sulfate (0.451μg/ml). In the study for thrombolytic property, different extracts of C. amada exhibited clot lysis ranging from 17.24 to 43.55% as compared to standard streptokinase (93.75 %). Dhaka Univ. J. Pharm. Sci. 19(1): 9-13, 2020 (June)